Stress indicators in the post-partum period and their relation with women's mood in the puerperium - Dolores Marín Morales; Francisco Javier Carmona Monge; Susana Toro Molina; Rocío Montejo Rodríguez; Cecilia Peñacoba Puente; Lilian Velasco Furlong; Isabel Carretero Abellán (Fundación para el Desarrollo de la Enfermería, 2013)
The aim of this research project is to study the relationships among physiological indicators of stress, maternal hormone levels and mood in the early postpartum, and their possible association with psychological problems during the puerperium. This observational, longitudinal and correlational study will be carried in a sample of voluntary women belonging to area 9 of health services of the Community of Madrid, the participants will be recruited during their childbirth hospitalization. To evaluate the target variables structured and validated questionnaires would be applied and analysis of biological indicators taken at two time points:-In the early postpartum: anxiety, depression and childbirth satisfaction, physiological indicators of the stress response (cortisol in saliva, plasma norepinephrine and epinephrine), and seric oxytocin and gonadotropin hormone levels. -During the puerperal period up to three months after delivery: perceived stress,anxiety and depression. Socio-demographic information as well as clinical data on the progress of labor, and status of maternal and neonatal health condition will be also obtained and included in the study.